On the approximation of functions from the Hölder class given on a segment by their biharmonic Poisson operators - Zhyhallo, K. M.; Zhyhallo, T. V. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.5 We obtain the exact equality for the upper bounds of deviations of biharmonic Poisson operators on the Hölder classes of functions continuous on the segment [-1;1].